2014
DOI: 10.1111/ejn.12809
|View full text |Cite
|
Sign up to set email alerts
|

Binding body and self in visuo‐vestibular conflicts

Abstract: Maintenance of the bodily self relies on the accurate integration of multisensory inputs in which visuo-vestibular cue integration is thought to play an essential role. Here, we tested in healthy volunteers how conflicting visuo-vestibular bodily input might impact on body self-coherence in a full body illusion set-up. Natural passive vestibular stimulation was provided on a motion platform, while visual input was manipulated using virtual reality equipment. Explicit (questionnaire) and implicit (skin temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 74 publications
(116 reference statements)
3
28
1
Order By: Relevance
“…We also build on our previous observations (Tieri et al ., ,b) by showing that experiencing conscious FO over a passively observed virtual hand is a slow process that develops over many seconds (~ 44.3 s from the start of the virtual hand's observation). Moreover, we expanded on previous evidence for the existence of a link between skin temperature and bodily illusions (Moseley et al ., ; Hohwy & Paton, ; Llobera et al ., ; Salomon et al ., ; Macauda et al ., ) by reporting that changes in strength of FO and VA over the virtual body were reflected by somato‐topic changes to the real body's skin temperature regulation. Analyses of thermal images showed (i) a significant modulation in skin temperature of both right and left hand, with a large temperature increase during the observation of m‐Wrist, Full‐Wood and m‐Wood (mean Δ T = ~ 0.14 °C) conditions and only a slight increase during the Full‐Limb condition (mean Δ T = ~ 0.02 °C) that had produced maximal embodiment scores; and (ii) that such effects occurred ~ 79 s after the start of the virtual hand's observation (~ 35 s after the conscious experience of illusory ownership had begun).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We also build on our previous observations (Tieri et al ., ,b) by showing that experiencing conscious FO over a passively observed virtual hand is a slow process that develops over many seconds (~ 44.3 s from the start of the virtual hand's observation). Moreover, we expanded on previous evidence for the existence of a link between skin temperature and bodily illusions (Moseley et al ., ; Hohwy & Paton, ; Llobera et al ., ; Salomon et al ., ; Macauda et al ., ) by reporting that changes in strength of FO and VA over the virtual body were reflected by somato‐topic changes to the real body's skin temperature regulation. Analyses of thermal images showed (i) a significant modulation in skin temperature of both right and left hand, with a large temperature increase during the observation of m‐Wrist, Full‐Wood and m‐Wood (mean Δ T = ~ 0.14 °C) conditions and only a slight increase during the Full‐Limb condition (mean Δ T = ~ 0.02 °C) that had produced maximal embodiment scores; and (ii) that such effects occurred ~ 79 s after the start of the virtual hand's observation (~ 35 s after the conscious experience of illusory ownership had begun).…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that acquiring SoE over an external object requires the convergence of two main sources of information: (i) the on‐line integration of bottom–up, congruent multisensory visuo‐tactile (Botvinick & Cohen, ; Ehrsson et al ., , ; Costantini & Haggard, ), visuo‐motor (Tsakiris et al ., ; Sanchez‐Vives et al ., ; Kalckert & Ehrsson, ), visuo‐spatial (Lloyd, ) and visuo‐vestibular (Lopez et al ., ; Macauda et al ., ) information; and (ii) the modulation of top–down information based on an internal body representation (Graziano & Botvinick, ; Makin et al ., ; Tsakiris, ). Here we showed that simple passive observation in 1PP is a sufficient condition for eliciting SoE over a virtual body even in the absence of multisensory stimulation and without any alteration of the peripersonal space.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They indicated an unbiased perception in the HMD view-based pose reproduction, which showed reliance on both visual and proprioceptive feedback. As for visuo-vestibular conflicts, Macauda et al employed questionnaire and skin temperature measures to assess illusory self-identification with either a mannequin or a control object [22]. They suggested an importance of congruence of the visual sense with the vestibular sense as in the HMAR.…”
Section: Expected Effectsmentioning
confidence: 99%